Literature Review on Database Design Testing Techniques - Abubakar Imam, A. (Springer Verlag, 2019)
Database driven software applications are becoming more sophisticated and complex. The behavior of these systems solely depends on the data being used. Whereas this data has now become so massive, varyingly connected, distributed, and stored and retrieved with different velocity, era of big data. To make these systems operate in every anticipated environment with the required usability, durability and security, they are subjected to rigorous testing using the available Software Testing Techniques (STT). This test is described as a process of confirming correct behavior of a piece of software which consists of three parts, namely, interface (GUI), back-end (codes) and data-source (database). The purpose of this study is to identify and analyze existing STT in the context of databases design structures. Primary studies related to ST were identified using search terms with relevant keywords. These were classified under journal and conference articles, book chapters, workshops, and symposiums. Out of the search results, 23 Primary studies were selected. Database testing has been significantly discussed in the software testing domain. However, it was discovered that, existing software testing techniques suffer from several limitations which includes: incompatibility with new generation databases, lack of scalability and embedded SQL query detection issues. In addition, application of existing techniques into a full-fledged software system has not been reported yet. Â© 2019, Springer Nature Switzerland AG.